All-optical quantitative framework for bioluminescence tomography with non-contact measurement - Chen, Xue-Li; Zhao, Heng; Qu, Xiao-Chao; Chen, Duo-Fang; Wang, Xiao-Rui; Liang, Ji-Min (International journal of automation and computing, 2012)
In this contribution, we present an all-optical quantitative framework for bioluminescence tomography with non-contact measurement. The framework is comprised of four indispensable steps: extraction of the geometrical structures of the subject, light flux reconstruction on arbitrary surface, calibration and quantification of the surface light flux and internal bioluminescence reconstruction. In particular, the geometrical structures are retrieved using a completely optical method and captured under identical viewing conditions with the bioluminescent images. As a result, the proposed framework avoids the utilization of computed tomography or magnetic resonance imaging to provide the geometrical structures. On the basis of experimental measurements, we evaluate the performance of the proposed all-optical quantitative framework using a mouse shaped phantom. Preliminary result reveals the potential and feasibility of the proposed framework for bioluminescence tomography.